Elasticity-related periodical Li storage behavior delivered by porous graphene. Issue 19 (2nd May 2017) - Ning, Guoqing; Cao, Yanming; Qi, Chuanlei; Ma, Xinlong; Zhu, Xiao
Abstract : Periodic variations of capacities and coulombic efficiencies are observed in the lithium insertion/extraction cycles of fibre-like graphene 3D networks, and the mechanism is explained. Abstract : Porous carbon materials have been widely used as active materials, additives or substrates in energy storage devices using Li + as the charge carrier. Fluctuations in cycling performance have been widely observed for Li storage by porous carbon materials, but the reason for such phenomena has not been clearly revealed. In this work, periodic variations of capacities and coulombic efficiencies are observed in the lithium insertion/extraction cycles of fibre-like graphene 3D networks. Volume expansion of nanopores in graphene networks caused by Li + accumulation and their elastic compression that leads to Li + release are considered as the key reasons for the periodic behavior. For the flexible few-layered graphene, the increase of the pore volume is retained, thus leading to a continuous increase of the Li storage capacity. Our results reveal a clear relationship between the elasticity of a porous carbon material and its Li storage performance.